2021
DOI: 10.25259/ijmio_31_2020
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Therapy for COVID-19 still has the potential to save lives - The ICMR PLACID study dissected

Abstract: Convalescent plasma therapy has been extensively used across the world and is believed to save the lives of COVID-19-positive patients. The early preprint release of ICMRs PLACID study results has set the cat among the pigeons. This study consisted of 464 patients across 25 cities in India, involving both government and private hospitals. Methodology and results have valid points on both sides of the argument. Its publication in a peer-reviewed journal is awaited so that the details can be ascertained accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[3,1] Stringent criteria for plasma donation like elapsing of minimum 28days post-recovery from symptoms, minimum 14 days post negative RT-PCR report, age 18-60 years, body weight >50kg, absence of comorbidity (hepatorenal; cardiopulmonary; uncontrolled diabetes; hypertension), nulliparity (more than half the women HCW have been pregnant earlier), would leave still fewer donors ideally suitable for CPT. [4] Donor-selection variations could explain the contradictory results of clinical trials and case-series on usefulness of CPT. [1,2,3]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,1] Stringent criteria for plasma donation like elapsing of minimum 28days post-recovery from symptoms, minimum 14 days post negative RT-PCR report, age 18-60 years, body weight >50kg, absence of comorbidity (hepatorenal; cardiopulmonary; uncontrolled diabetes; hypertension), nulliparity (more than half the women HCW have been pregnant earlier), would leave still fewer donors ideally suitable for CPT. [4] Donor-selection variations could explain the contradictory results of clinical trials and case-series on usefulness of CPT. [1,2,3]…”
Section: Discussionmentioning
confidence: 99%
“…Convalescent plasma therapy (CPT) has been widely endorsed. [1,2,3,4] However, the multicentric PLACID-trial findings report no difference in 28-day mortality between the intervention group patients (two 100ml doses of convalescent plasma) and the control group. [2] It is important to gauge the existence, extent and duration of this immunity in COVID-survivors and this is the research question we seek to answer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such patients deserve aggressive treatment for the coronavirus infection like other noncancer patients. 45 , 46 …”
Section: Methodsmentioning
confidence: 99%
“…An open label, parallel arm, phase II, multicenter, randomized controlled trial conducted in India showed that convalescent plasma was not associated with a reduction in progression to severe COVID-19 or all-cause mortality. 9 10 However it was noted that CPT was associated with earlier resolution of shortness of breath and fatigue and higher negative conversion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA on day seven of enrolment. This finding opened discussion regarding the use of CPT earlier in disease course, possibly reducing progression to severe disease and acting as a bridge for recovering patients.…”
Section: Negative Studiesmentioning
confidence: 99%